2022
DOI: 10.3389/fcimb.2022.998748
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic prospects of ceRNAs in COVID-19

Abstract: Since the end of 2019, COVID-19 caused by SARS-CoV-2 has spread worldwide, and the understanding of the new coronavirus is in a preliminary stage. Currently, immunotherapy, cell therapy, antiviral therapy, and Chinese herbal medicine have been applied in the clinical treatment of the new coronavirus; however, more efficient and safe drugs to control the progress of the new coronavirus are needed. Long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) may provide new therapeutic targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…At this point, we focused on lncRNAs because several studies have reported their association with COVID-19. [74][75][76] In this section, XIST was omitted because changes in its expression were reported in infected mouse cells (not human cells). In addition, as shown in Figure 6f, several studies have confirmed some differences in the expression of MALAT1 and NEAT1 in different human cells or human PBMCs infected with SARS-CoV-2.…”
Section: Cerna Network Of Mrna-mirna-lncrnamentioning
confidence: 99%
“…At this point, we focused on lncRNAs because several studies have reported their association with COVID-19. [74][75][76] In this section, XIST was omitted because changes in its expression were reported in infected mouse cells (not human cells). In addition, as shown in Figure 6f, several studies have confirmed some differences in the expression of MALAT1 and NEAT1 in different human cells or human PBMCs infected with SARS-CoV-2.…”
Section: Cerna Network Of Mrna-mirna-lncrnamentioning
confidence: 99%
“…49 Studies have revealed lncRNAs like MALAT1 and TUG1 as regulators of inflammatory factors such as IL-6 and NLRP3, with implications for cardiovascular disease. 68 Further research uncovered that lncRNAs such as MIR503HG and NFIA-AS1 regulate apoptosis, ECM integrity, and inflammation in vascular disease contexts. 46,69,70…”
Section: Long Noncoding Rna and Reactive Oxygen Species In Vascular S...mentioning
confidence: 99%
“…The regulation of miRNAs by TFs is critical, and aberrant regulation of miRNAs by TFs can cause phenotypic variations and diseases 89 . In addition, as competitive endogenous RNA (ceRNA), lncRNA and circRNA competitively bind miRNA through miRNA response elements (MREs) to inhibit mRNA degradation mediated by miRNAs targeting, which is reflected in lncRNA/circRNA-miRNA-mRNA cascade regulation network 88 , 90 . LncRNAs can also be used as miRNA precursors, which can generate specific miRNAs by intracellular RNA cleavage and enhance the post-transcriptional regulation of target mRNAs 91 .…”
Section: Circulating Mirnas Involving In Covid-19-related Organ Dysfu...mentioning
confidence: 99%